2008
DOI: 10.1007/s00412-008-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Coprinus cinereus Mer3 is required for synaptonemal complex formation during meiosis

Abstract: Mer3 is an evolutionarily conserved DNA helicase that has crucial roles in meiotic recombination and crossover formation. We have identified the MER3 homolog in Coprinus cinereus (Ccmer3) and show that it is expressed in zygotene and pachytene meiocytes. Immunostaining analysis indicated that CcMer3 was localized on chromosomes at zygotene and pachytene and CcMer3 foci were more frequent on paired than unpaired chromosomes. We generated a C. cinereus mer3 mutant (#1) and found that it showed abnormal meiosis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Of the 74 S. cerevisiae and/or S. pombe meiotic genes surveyed, 57 were found to have homologs in the A. cinnamomea genome (SI Appendix, Table S6 and Dataset S1), including those that are "meiosisspecific" and hypothesized to be present only in organisms with sexual reproduction or with sexual ancestry. The A. cinnamomea genome encodes several evolutionarily conserved proteins required for assembling the synaptonemal complex, e.g., mer3 (ACg003801), msh4 (ACg005375), msh5 (ACg002475), and zip4/spo22 (ACg005454) (SI Appendix, Table S6 and Dataset S1), suggesting that A. cinnamomea, like most sexually reproductive organisms, forms the synaptonemal complex to mediate chromosomal synapsis, allowing interacting homologous chromosomes to complete their crossover activities during meiosis (25).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 74 S. cerevisiae and/or S. pombe meiotic genes surveyed, 57 were found to have homologs in the A. cinnamomea genome (SI Appendix, Table S6 and Dataset S1), including those that are "meiosisspecific" and hypothesized to be present only in organisms with sexual reproduction or with sexual ancestry. The A. cinnamomea genome encodes several evolutionarily conserved proteins required for assembling the synaptonemal complex, e.g., mer3 (ACg003801), msh4 (ACg005375), msh5 (ACg002475), and zip4/spo22 (ACg005454) (SI Appendix, Table S6 and Dataset S1), suggesting that A. cinnamomea, like most sexually reproductive organisms, forms the synaptonemal complex to mediate chromosomal synapsis, allowing interacting homologous chromosomes to complete their crossover activities during meiosis (25).…”
Section: Resultsmentioning
confidence: 99%
“…The mer3 mutant reduces the frequency of crossovers, and the remaining crossovers are distributed randomly along the chromosomes. Recently, homologs of MER3 were identified from Arabidopsis (Mercier et al 2005), humans (Tanaka et al 2006), Coprinus cinereus (Sugawara et al 2009) and rice (Wang et al 2009). In Arabidopsis, the Atmer3 mutation leads to defective crossover formation (Mercier et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…In Arabidopsis, the Atmer3 mutation leads to defective crossover formation (Mercier et al 2005). Sugawara et al (2009) reported that SC formation was defective although AEs were present in the Ccmer3 mutant of C. cinereus. Therefore, CcMER3 is required for the formation of SC after the AEs become aligned and is essential for the homologous synapsis.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, meiosis and basidiospore formation is not required for fruiting body maturation. Defects in meiosis or in subsequent sporulation leads still to fully erected, normal-shaped mushrooms that however have caps of whitish appearance ('white caps') due to lack of spore formation or coloration and such white caps still may undergo autolysis (Zolan et al, 1988;Kanda et al, 1989;Lu et al, 2003;Namekawa et al, 2005;Sugawara et al, 2008).…”
Section: Coprinopsis Cinerea Psathyralleceae Agaricales Agaricomycmentioning
confidence: 98%